In search of new trends - Maciej Stawny (Polskie Towarzystwo Farmaceutyczne, 2023)
This issue presents a collection of selected papers from the International Conference NEW TRENDS in Polish and global pharmacy: Science, business, and modern education, which took place on September 29-30, 2022, Poznań, Poland. The conference aimed to develop an effective communication platform between science and business. Prominent specialists in science, education, and business who deal with the issues of developing bridges between these three sectors participated in the event. Scientific achievements, the latest research results, and the potential of medical universities as an offer for the pharmaceutical industry were presented.